Towers on the steppe: compact city plans and local perceptions of urban densification in Ulaanbaatar, Mongolia. Issue Volume 10:Issues 2(2017) (3rd April 2017) - Anderson, Raven; Hooper, Michael; Tuvshinbat, Aldarsaikhan
Abstract: This paper examines how plans for urban densification, particularly those supported by international organisations, intersect with local residents' perceptions of housing and land use in the developing world. The study focuses on ger districts in Ulaanbaatar, the site of numerous plans for large-scale urban transformation. Ger districts are rapidly growing areas named for the felt tents that are considered their typical housing mode. This study interviewed 120 ger district residents across central, middle and outer areas of the city. The results reveal migration patterns different from those typically reported, with the highest proportions of migrants and renters living in the central district. Interviewees generally held positive views of apartment living, while preferring low-density land use. Residents' views of density were strongly influenced by Mongolian attitudes to land and open space. The paper concludes by discussing the reasons for, and consequences of, residents' and international policy-makers' different framings of urban density.